Caffeine and performance in clay target shooting - Share, B.; Sanders, N.; Kemp, J. (Journal of Sports Sciences, 2009)
Controversy surrounds the influence that caffeine has on accuracy and cognitive performance in precision activities such as shooting and archery. The aim of this study was to assess the effects of two doses of caffeine on shooting performance, reaction time, and target tracking times in the sport of clay target shooting. A randomized, double-blind, placebo-controlled design was undertaken by seven elite male shooters from the double-trap discipline. Three intervention trials (2 mg caffeine/kg body mass (BM); 4 mg caffeine/kg BM; placebo) were undertaken, in which shooters completed four rounds per trial of 50 targets per round. Performance accuracy (score) and digital video footage (for determination of reaction time and target tracking times) were gathered during competition. Data were analysed using repeated-measures analysis of variance. No differences in shooting accuracy, reaction time or target tracking times among the three intervention trials or across the four rounds within each intervention were observed (P > 0.05). The results indicate that ingestion of =4 mg caffeine/kg BM does not provide performance benefits to elite performers of clay target shooting in the double-trap discipline.